Introduction: Ethnographies of Corporate Ethicizing - Dolan, C; Rajak, D (2011)
As the global community confronts increasing economic, social, and environmental challenges, the corporate social responsibility (CSR) movement has demonstrated a powerful capacity to offer itself up as a solution, circulating new ethical regimes of accountability and sustainability in business. This article introduces five contributions that explore ethnographically the meanings, practices, and impact of corporate social and environmental responsibility across a range of transnational corporations and geographical locations (India, South Africa, the UK, Chile, and the Democratic Republic of the Congo). In each of these contexts corporations are performing ethics in different ways and to different ends, from the mundane to the ritualistic and from the discursive to the material, drawing a range of actors, interests, and agendas into the moral fold of CSR. Yet across these diverse sites a set of common tensions in the practice and discourse of CSR emerge, as the supposedly “win-win“ marriage between the social and the technical, the market and morality, and the natural and the cultural becomes routinized in global management practice. By tracing the connections and conflicts between the local micropolitics of corporate engagement and the global movements of CSR, the collection reveals the ambiguous and shifting nature of CSR and the ways in which social and environmental relations are transformed through the regime of ethical capitalism.